Resistance of concrete to chloride ingress : testing and modelling - Tang, Luping 1956- (Spon Press, 2012)
"Chloride ingress in reinforced concrete induces corrosion and consequent spalling and structural weakness, and it occurs world-wide and imposes an enormous cost. Yet it can be resisted by using test methods and relevant models for service life prediction. Resistance of Concrete to Chloride Ingress sets out current understanding of chloride transport mechanisms, test methods and prediction models. It describes basic mechanisms and theories, and classifies the commonly used parameters and their units which expressing chloride and its transport properties in concrete. Laboratory test methods and in-field applicable test methods, including precision results from inter-laboratory comparison tests, are then outlined. Some of the fundamentals of models are explained, and the different types of models are then analyzed theoretically and critically. Analytical and probabilistic approaches are used to analyze the sensitivity of various models and the results from a benchmarking evaluation of different models are presented and discussed. Guidelines for the practical use of test methods and models are given, including tests for in-situ applications, and test methods validated by the precision results are detailed. The book draws to a large extent on the Chlortest project, which involved seventeen partners from ten European countries, and serves as an authoritative guide"--